2006
DOI: 10.1038/sj.ki.5001727
|View full text |Cite
|
Sign up to set email alerts
|

The use of contrast media in deceased kidney donors does not affect initial graft function or graft survival

Abstract: Patients receiving cadaveric kidney transplants often experience delayed graft function. As iodinated contrast media injection (ICMI), necessary for cerebral angiography, which is often used to diagnose brain death, can be nephrotoxic, we compared renal function recovery (RFR) and 1-year and long-term graft survival according to the method used to diagnose brain death. Data from 9921 cadaveric kidneys, transplanted between 1 January 1998 and 31 December 2003, were retrieved from the French National Registry fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
1
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 37 publications
2
15
1
1
Order By: Relevance
“…The latter is considered a risk factor for impaired kidney function, although it has been reported that the use of contrast causes no nephrological damage that could invalidate the use of the kidney for transplant [35].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The latter is considered a risk factor for impaired kidney function, although it has been reported that the use of contrast causes no nephrological damage that could invalidate the use of the kidney for transplant [35].…”
Section: Discussionmentioning
confidence: 98%
“…It may be also useful when considering organ donation since it avoids delays in managing the potential donor. Although the patients included in our study were not sedated, their lack of CBF precludes the possibility of any neurological activity such that this criterion of a confirmed lack of blood flow in the brain will always determine an unequivocal diagnosis of brain death even in sedated patients [22,35].…”
Section: Discussionmentioning
confidence: 99%
“…No significant increase in the prevalence of delayed graft function or reduction in graft survival has been associated with perimortem donor contrast studies (257,269,270).…”
Section: Can a Kidney Be Accepted From A Donor Who Has Received IV Comentioning
confidence: 98%
“…The current recommendations are to keep the administered contrast to a minimum, which is nonspecific (13,14). Park et al described the use of iodinated contrast:estimated glomerular filtration rate (eGFR) ratio for predicting contrast-induced acute kidney injury (AKI) in patients undergoing percutaneous coronary intervention for myocardial infarction (15), but to date this metric has not been evaluated within the KTR population.…”
Section: Introductionmentioning
confidence: 99%